UPAYA PENGENDALIAN SAMPAH SEBAGAI BENTUK IMPLEMENTASI GERAKAN ZERO WASTE DI DESA TANJUNG LUAR - Riskiani, Mira; Muta’Aly, Abdullah Ali; Hafida, Hafida; Paris, Muhamad; Fajrin, M.Arya Bima; Syahputra, Ragil rahmat; Sabrina, Lona; Loka, Selinda Ayu Pidya; Hermansyah, Sabrina Aisya; Fitriani, Winda (Universitas Mataram, 2024)
Field Study and Community Service Program (KKN) is a learning activity designed for students to apply their knowledge and technology in the mid of society for the welfare for society it self. The 2024 PMD KKN program implemented in Tanjung Luar Village raises the theme of Zero Waste and blue economy as the basic foundation of the main KKN program, waste control activities and creative economy are carried out as programs to develop village potential. The purpose of the 2024 PMD KKN program is to solve the problems that exist in Tanjung Luar Village, especially those related to waste. The program methods carried out in KKN consist of (1) Socialization to the village community, (2) procurement of TPS landfills in the village environment, (3) mutual cooperation activities with the community to clean up garbage, (4) cultivating maggot as education and alternative organic waste processing, (5) teaching students about healthy and clean lifestyles. The results of these activities can provide benefits to the community and help overcome existing problems, through the main programs of blue economy and zero waste can help open up new potentials, especially in the village economy, programs from KKN students are successfully achieved by providing awareness and insight to the community about waste control, making TPS at various points of the village environment, cultivating maggot as an alternative to organic waste processing, cleaning the beach through gotong royong, and briefing the younger generation on how to implement a clean and healthy lifestyle. The work program that has been carried out for a month by students is expected to be able to answer the problems of Tanjung Luar Village and help advance the potential of the village from the economy and tourism.